2018
DOI: 10.2166/washdev.2018.169
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water security and source preferences in rural Tanzania

Abstract: The public health and well-being of people in many rural communities in developing countries suffer due to poor water resources management and undesirable agricultural practices. This study was conducted in a pastoral community in northern Tanzania. The objective was to identify the most reliable water source in terms of quality and access from three main water sources: surface water, shallow wells, and deep wells. The Water Quality Index (WQI) was used to assess the overall water quality and was determined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Water testing results showed that the water sources used by the school are not safe for drinking due to poor hygiene and unprotected water sources (Ngasala et al 2018(Ngasala et al , 2019a. From the study, it is found that there is a lack of awareness on the domestic water treatment methods and practices with only 17% of the participants knowing about chlorination.…”
Section: Discussionmentioning
confidence: 93%
“…Water testing results showed that the water sources used by the school are not safe for drinking due to poor hygiene and unprotected water sources (Ngasala et al 2018(Ngasala et al , 2019a. From the study, it is found that there is a lack of awareness on the domestic water treatment methods and practices with only 17% of the participants knowing about chlorination.…”
Section: Discussionmentioning
confidence: 93%
“…For use as an emergency backup water source, local alternative water sources need to be independent from the current primary water intake (WA DOH, 2017a) and compatible with the existing water supply system (OU, 2016). The alternative water source also needs to be evaluated to determine the potential amount of current demand that can be met with consideration of seasonal variations (Ngasala et al, 2018) and distance from existing infrastructure in relation to cost (Marsden et al, 2006; OECD, 2007). The volume of water that an alternative source can provide during an emergency can be calculated as the amount of water in storage plus the volume supplied by alternative water supply minus current system demand.…”
Section: Selected Countermeasures and Their Contribution To Resiliencementioning
confidence: 99%
“…Also, Gerlak et al (2018) suggest that the scholars often adapt the water security concept to the contexts of the cases they are studying. Nonetheless, most of the existing assessments are focused on the national, regional or city scales, and a very few studies have recently started to focus on the rural scale (Penn et al , 2017; Ngasala et al , 2018; Sen and Kansal, 2019; Shah, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%